Photosynthetic Response of Blueberries Grown in Containers - Melba R. Salazar-Gutiérrez; Kathy Lawrence; Elina D. Coneva; Bernardo Chaves-Córdoba (Plants, 2023)
Recently, there has been increased interest in container blueberry production as a viable alternative to open-field blueberry planting. Container production of blueberries offers numerous advantages, among these, a lack of limitation by suboptimal soil conditions in the open field and the ability to control substrate pH, drainage, and organic matter. The photosynthetic response for three container-grown Southern highbush blueberry (interspecific Vaccinium hybrids) cultivars including ‘Jewel’, ‘Meadowlark’, and ‘Victoria’ and a rabbiteye blueberry (Vaccinium virgatum) ‘Baldwin’, were measured during the spring and summer of 2022. It was hypothesized that the three cultivars evaluated would have different photosynthetic responses. The objective of this study was to determine the photosynthetic activity of different blueberry cultivars during the first year of crop establishment. A series of measurements were conducted every 2 h throughout the day and for different dates using a gas exchange data analyzer on newly matured fully expanded leaves located in the top middle section of the canopy for each cultivar. The response curves showed that net photosynthesis (A) became saturated at moderate light, with saturation occurring at a photosynthetic photon flux density (PPFD) of 1932 µmol m−2 s−1. At this point, the rate of CO2 assimilation was approximately 16.84 µmol CO2 m−2 s−1. No differences in (A) were found among cultivars. Overall, the attained values of photosynthesis provide a strong conceptual basis for understanding the cultivar variation response when grown in containers; therefore, the containerized system may serve as a production system for early fruiting blueberries in Alabama, USA.